Perforator plus flaps: Optimizing results while preserving function and esthesis - Mehrotra Sandeep (Indian Journal of Plastic Surgery)
Background: The tenuous blood supply of traditional flaps for wound cover combined with collateral damage by sacrifice of functional muscle, truncal vessels, or nerves has been the bane of reconstructive procedures. The concept of perforator plus flaps employs dual vascular supply to flaps. By safeguarding perforators along with supply from its base, robust flaps can be raised in diverse situations. This is achieved while limiting collateral damage and preserving nerves, vessels, and functioning muscle with better function and aesthesis. Materials and Methods: The perforator plus concept was applied in seven different clinical situations. Functional muscle and fasciocutaneous flaps were employed in five and adipofascial flaps in two cases, primarily involving lower extremity defects and back. Adipofascial perforator plus flaps were employed to provide cover for tibial fracture in one patients and chronic venous ulcer in another. Results: All flaps survived without any loss and provided long-term stable cover, both over soft tissue and bone. Functional preservation was achieved in all cases where muscle flaps were employed with no clinical evidence of loss of power. There was no sensory loss or significant oedema in or distal to the flap in both cases where neurovascular continuity was preserved during flap elevation. Fracture union and consolidation were satisfactory. One patient had minimal graft loss over fascia which required application of stored grafts with subsequent take. No patient required re-operation. Conclusions: Perforator plus concept is holistic and applicable to most flap types in varied situations. It permits the exercise of many locoregional flap options while limiting collateral functional damage. Aesthetic considerations are also addressed while raising adipofascial flaps because of no appreciable donor defects. With quick operating times and low failure risk, these flaps can be a better substitute to traditional flaps and at times even free tissue transfers.